(untitled) (Journal of International Crisis and Risk Communication Research, 2022)
The COVID-19 pandemic has disproportionately affected African American college students and put them at high risk of mental health concerns. Guided by the community resilience model, this study examined how Historically Black Colleges and Universities (HBCUs) communicated mental health resources during the COVID-19 pandemic. An analysis of HBCUs’ website-based communication showed that mental health received minimal importance in response to the ongoing pandemic. Although larger and advanced degree-granting institutions provided a relatively greater amount of mental health resources than smaller institutions, those resources might not be sufficient to buffer against the COVID-19 induced stressors. Providing such inadequate mental resources indicate that many HBCU institutions were unable to provide a necessary supportive environment for the campus communities. HBCUs may establish formal and informal networks with local and regional mental health support organizations and share resources. Specifically, smaller institutions would benefit from such networked support. Additionally, HBCUs need to prioritize mental health in their response to COVID-19 to promote resilience among the student community.